The water tap design for ablution activities considering cultural influences: a design for sustainability - Ghazali, Ihwan; Padzil, Nur Wardah Sufina; Mohamad, Effendi Bin; Al-Mashjari, Layla Ahmed; Irianto, Irianto; Herawan, Safarudin Gazali (Frontiers in Environmental Science, 2023)
Water is a vital resource that should be utilised effectively. Yet However, it is overused and squandered on a daily basisneed,; including the unrestrained use of water for ablution purposes. This condition can be due to a lack of awareness and the influences of peer cultural valuevalues. Therefore, the aim of this study is to develop a water-tap design that takes into consideration the influences of cultural value. Accordingly, confirmatory factor analysis and the structural equation modelling (SEM) evaluated approach the significant correlation between cultural influences and user preferences on water-tap design by referring at the critical threshold output of each attribute. The result showed that collectivism and uncertainty avoidance dimensions waswere identified as the influencing cultural dimensions and the automatic water level-control float valve, mechanical water tapswater-taps with auto-stop function, and transparent water tanks are the most important consideration considerations for water tap technical specification. Through the assessment of its applicability, the use of the prototype can reduce water usage by 54.6% compared to regular water tapswater-taps. The proposed water-tap design is a promising solution for reducing water consumption in ablution activities while considering cultural influences. Correspondingly, , the approach of cultural value in the designing process is expected to give more insights to practices such as product designers when determining design specification while for knowledge, it extends the applicability of Hofstede cultural theory for product design and development.the implications for theory and recommendation are also discussed to support the water conservation and environmental sustainability practice. Style Definition: UTEM PARA 1: Don't add space between paragraphs of the same style, Tab stops: 3.06", Left Commented [I-1]: Background statement